Cascade observers for output-feedback control under parametric uncertainties, disturbances and arbitrary sensor delays. Issue 9 (1st September 2020) - Marques, Ionara Oliveira; Oliveira, Tiago Roux; Cunha, José Paulo V. S.
ABSTRACT: An output-feedback control system for uncertain linear systems with arbitrary delay in the output signal and input disturbances is developed. The state of the system and the disturbances are estimated by observers connected in cascade. Unlike previous works, parametric uncertainties are allowed. Their effects are analysed by using the Small-Gain Theorem. The rejection of the exogenous and matched input disturbances is also considered in the system. The proposed control strategy guarantees global stability of the closed-loop system. A numerical example and an application to underwater vehicle control illustrate the effectiveness of the proposed control strategy to compensate arbitrary delays, disturbances and bounded uncertainties.